Sensory texture profiling and development of standard rating scales for pounded yam - Otegbayo, B.; Aina, J.; Sakyi-Dawson, E.; Bokanga, M.; Asiedu, Robert (Wiley, 2005)
This study evaluated sensory texture profile analysis (STPA) as an objective method for characterizing the texture attributes of “pounded yam,” a popular dish in West Africa made by peeling yam, boiling, pounding and kneading it into a glutinous dough. Panelists were carefully selected and trained to assess the texture attributes of pounded yam. Standard rating scales were developed from local foods that are common in Nigeria, and the foods were used as descriptors to exemplify the texture attributes being assessed. Reproducible and consistent results were obtained. It is thus concluded that STPA can be used as an objective method for evaluating the texture attributes of pounded yam.